2017
DOI: 10.1039/c7lc00210f
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous electrical recording of cardiac electrophysiology and contraction on chip

Abstract: Prevailing commercialized cardiac platforms for in vitro drug development utilize planar microelectrode arrays to map action potentials, or impedance sensing to record contraction in real time, but cannot record both functions on the same chip with high spatial resolution. Here we report a novel cardiac platform that can record cardiac tissue adhesion, electrophysiology, and contractility on the same chip. The platform integrates two independent yet interpenetrating sensor arrays: a microelectrode array for fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 38 publications
2
92
0
Order By: Relevance
“…Norepinephrine exerts its effect by activating β1 receptors enhancing the contraction of cardiomyocytes while the signal amplitude remains unchanged, see the Supporting Information. Notably, given the different protein expression from cell to cell and the drug injection location, the time‐dependent traces (Figure S10, Supporting Information) and real‐time map reveal a remarkable change of the action potential propagation after administration of norepinephrine. The initial activation spot of action potential shifted from OECT 10 (6, 5) (Figure b) to OECT 1 (2, 6) (Figure c), accompanied by a reversed propagation direction.…”
Section: Resultsmentioning
confidence: 99%
“…Norepinephrine exerts its effect by activating β1 receptors enhancing the contraction of cardiomyocytes while the signal amplitude remains unchanged, see the Supporting Information. Notably, given the different protein expression from cell to cell and the drug injection location, the time‐dependent traces (Figure S10, Supporting Information) and real‐time map reveal a remarkable change of the action potential propagation after administration of norepinephrine. The initial activation spot of action potential shifted from OECT 10 (6, 5) (Figure b) to OECT 1 (2, 6) (Figure c), accompanied by a reversed propagation direction.…”
Section: Resultsmentioning
confidence: 99%
“…Yang Jianmin et al [91] reported the first microfluidic devices to achieve cardiac myocytes (CMs) anisotropy ( Figure 3A). Qian et al [92] constructed a cardiac chip that consists of a microelectrode array (MEA) for potential field indication and an interleaved electrode array for conversion. The platform uses transplantation of cardiomyocytes (CMs) derived from human induced pluripotent stem cells (hiPSC-CMs) to measure the electrophysiology and contractility of myocardial cells under physiological conditions and drug stimulation, respectively.…”
Section: Heart-on-a-chip For Drug-induced Cardiotoxicity Testingmentioning
confidence: 99%
“…For a more thorough review of currently available OOCs, refer to these reviews (An et al, 2015;Esch et al, 2015;Balijepalli and Sivaramakrishan, 2017;Low and Tagle, 2017;Kimura et al, 2018). Although they each started with simplistic models, each of these platforms has now been advanced to adapt novel physiologically relevant functions such as cellular contractions (i.e., heart, lung, and eye) (Huh, 2015;Qian et al, 2017;Seo et al, 2019), drug synthesis and excretion (i.e., liver and kidney) (Paoli and Samitier, 2016;Deng et al, 2019), barrier functions (i.e., skin and brain) (Jeong et al, 2018;Mieremet et al, 2019), dynamic flow of blood, air, or fluid interfaces (i.e., heart, lung) (Ribas et al, 2016;Artzy-Schnirman et al, 2019), and even co-culture with bacterial microbiomes (i.e., intestine) (Jalili-Firoozinezhad et al, 2019) in order to replicate the human organ systems of interest. In addition, multiple organ chips can be integrated, either physically through tubing or microfluidic channels or virtually by sending effluents from one OOC to another OOC, to create in vitro models of interconnected organ systems, with the ultimate goal of mimicking the entire human physiology (Maschmeyer et al, 2015;Materne et al, 2015;Kimura et al, 2018;Ramme et al, 2019).…”
Section: Introductionmentioning
confidence: 99%